KARAKTERISASI DAN HUBUNGAN KEKERABATAN 13 GENOTIPE SORGUM (Sorghum bicolor (L.) Mouch KOLEKSI BATAN - Ricardo Panjaitan; Elza Zuhry; Deviona ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The objective of the research was to study the agronomic characteristics ofsorghum and studying genetic relationships genotypes of 13 sweet sorghum. Thisresearch  has  been  carried  on  in  the  field  experiment  and  Plant  BreedingLaboratory,  Faculty  of  Agriculture,  University  of  Riau,  Pekanbaru, from April2013 to September 2013.The data were examined by analysis of variance consistof 13 treatments and 3 replications that contained 39 experimmental units. Thesetreatments consist of BATAN’s sweet sorghum strains, there are Patir-1, Patir-2,Patir-3, Patir-4, Patir-5, Patir-6, Patir-7, Patir-8, Patir-9, Patir-10 and 3 sweetSorghum  varieties  as  a  comparison,  there  are  Kawali,  Mandau  and  Pahat.GenotypePatir-10 has the highest of seed weight are 3.78 ton/ha compare to othergenotypes.  The results of the research  showed that clusters are the differencesand similarities between the 13 sorghum genotypes tested on quantitative andqualitative variables.  Based  on  the cluster analysisPatir 2 and  Patir 3 are genotype that has nearst genetic with the lowest genetic  distance is 1.71. Patir 9 and Mandau have farthest genetic relationship with the highest genetic distance is 84.24.   Keywords : characteristic, relationship, sorghum and Cluster Analysis.